Comparison of the respiratory bacterial microbiome in cats with feline asthma and chronic bronchitis - Werner, Melanie; Weeger, Jasmin; Hörner-Schmid, Lina; Weber, Karin; Palić, Jelena; Shih, Jonathan; Suchodolski, Jan S.; Pilla, Rachel; Schulz, Bianka (Frontiers in Veterinary Science, 2023)
Objectives While feline chronic bronchitis (CB) is known as neutrophilic bronchial inflammation (NI), feline asthma (FA) is defined as an eosinophilic airway inflammation (EI). Feline chronic bronchial disease refers to both syndromes, with similar clinical presentations and applied treatment strategies. Recent studies described alterations of the microbiota composition in cats with FA, but little is known about the comparison of the lung microbiota between different types of feline bronchial disease. The study aimed to describe the bacterial microbiota of the lower respiratory tracts of cats with FA and CB and to identify potential differences. Methods Twenty-two client-owned cats with FA (n=15) or CB (n=7) confirmed via bronchoalveolar-lavage (BALF)-cytology were included. Next-generation sequencing analysis of 16S rRNA genes was performed on bacterial DNA derived from BALF samples. QIIME was used to compare microbial composition and diversity between groups. Results Evenness and alpha-diversity-indices did not significantly differ between cats with FA and CB (Shannon p=0.084, Chao 1 p=0.698, observed ASVs p=0.944). Based on a PERMANOVA analysis, no significant differences were observed in microbial composition between animals of both groups (Bray-Curtis metric, R-value 0.086, p=0.785; unweighted UniFrac metric, R-value -0.089, p=0.799; weighted Unifrac metric, R-value -0.072, p=0.823). Regarding taxonomic composition, significant differences were detected for Actinobacteria on the phylum level (p= 0.026), Mycoplasma spp. (p= 0.048), and Acinetobacteria (p= 0.049) on the genus level between cats with FA and CB, with generally strong interindividual differences seen. There was a significant difference in the duration of clinical signs before diagnosis in animals dominated by Bacteriodetes (median 12 months, range 2 to 58 months) compared to animals dominated by Proteobacteria (median one month, range one day to 18 months; p=0.003). Conclusions and relevance Lung microbiota composition is very similar in cat populations with spontaneous FA and CB besides small differences in some bacterial groups. However, with disease progression, the lung microbiome of cats with both diseases appears to shift away from dominantly Proteobacteria to a pattern more dominated by Bacteriodetes. A substantial proportion of cats tested positive for Mycoplasma spp. via sequencing, while none of them tested positive using classical PCR.